The Migration of Dalmatian Pastoral Populations from the Perspective of the French Administrators of this Province (1806–1813) - Sajkowski, Wojciech (Sensus Historiae, 2024)
This paper focuses on the problem of the migration of the pastoral populations of Dalmatia from the perspective of the French administrators of this province (1806–1813). It deliberates more on the technical aspects of the French attempts to exploit the military potential of Dalmatian society, rather than on the deeper descriptions of the local pastoral population. The analyzed documents prove that at the beginning of the 19th century, the majority of the populations living in Dalmatia were still engaged in traditional pastoralism. The French did not manage to change this way of life, as their presence in Dalmatia lasted only from 1806 to 1813. However, their attempts to do so are part of a larger trend that can also be seen in other parts of Europe where traditional pastoralism functioned. The modern state, which developed in the 19th century and controlled more and more aspects of society, could not allow the existence of activities with a clearly cross-border and transnational character.